Pembelajaran Interaktif (Game What The Code) : Pengembangan Aplikasi Quiz Untuk Meningkatkan Kemampuan Pemrograman Pengguna Dengan Berbagai Bahasa Pemrograman - Ashadi, Ninik Rahayu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study is to determine the results of the development of the Quiz Game Application what the code to improve user programming skills with various programming languages. The research method used is research and development (Research and Development / R & D) which aims to design, develop, and test the effectiveness of an interactive quiz game application called What the Code in improving user programming skills in various programming languages. Research Results The results of the study are arranged based on the ADDIE development model, but the development model does not reach the Evaluation stage. The following are the results: (1) Analysis: based on the results of the analysis of user needs, curriculum, and general difficulties in learning programming, (2) Design: Designing game structures, question scenarios, multi-language features using programming languages (Java, JavaScript), and gamification systems. (3) Development: Application development with technology frameworks according to needs (React Native and Flutter). Based on the results of the study, it can be concluded that the quiz application developed using the ADDIE method can improve user programming skills with various programming languages.